STRENGTHENING ACCOUNTABILITY MECHANISMS IN WAQF INSTITUTIONS: A SYSTEMATIC LITERATURE REVIEW - Fauziyah Latiefa Salsabila; Rini; M Fahmi Hidayat (Journal of Sharia Economics, 2024)
Waqf institutions have faced several challenges in carrying out their functions and duties, including accountability issues that may hinder the growth and sustainability of waqf institutions. This journal aims to conduct a methodical review of the being literature on strengthening responsibility or accountability mechanisms in waqf institutions. Designed as a systematic study, it reviews articles published on scopus and google scholar from 2014 to 2024. The findings of this journal can provide insights and suggestions for the strengthening of appropriate accountability mechanisms, and it is hoped that waqf institutions can contribute more effectively in fulfilling their social objectives and strengthening the presence of Islam in society. Based on the systematic literature review, the article identifies three main dimensions relating to waqf institutions, namely: processes, institutional framework, and reporting techniques. The literature analysis also highlights the importance of cooperation between internal and external parties in strengthening accountability mechanisms within waqf institutions.